Nanosecond Self-Q-Switching Nd:Luag Laser With High Repetition Rate - Guangju Zhang; Qiang Liu; Peilin Li; Xing Fu (IEEE Photonics Journal, 2021)
Numerical and experimental studies were investigated for the self-Q-switching Nd:LuAG laser which was achieved by the Kerr lens effect. By applying two output couplers of 6% and 1.4%, the shortest pulses of 193.4 ns and 5.1 ns were generated respectively while the corresponding repetition rates were 1.175 MHz and 96.15 MHz respectively. Related to the average powers of 3.34 W and 2.56 W, the system demonstrated the optical to optical efficiency of 21.87% and 21.1% for coupler of 6% and 1.4% respectively. The short pulses with the high repetition rates can be applied in many fields which demonstrate the high value of the research on this self-Q-switching laser.